1987
DOI: 10.3109/02770908709070924
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Hyperresponsiveness in Children with Atopic and Nonatopic Asthma

Abstract: We have studied the bronchial hyperresponsiveness of children with atopic and nonatopic asthma by methacholine inhalation challenge, using a new device, the "Astograph." Three parameters, initial respiratory resistance (Rrs cont), bronchial sensitivity (Dmin), and bronchial reactivity (St), were studied. The Rrs cont values of atopic asthma were higher than those of the disease controls (p less than 0.05), while there was no difference between nonatopic asthma and disease controls. The Dmin values of atopic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…11,15 Recently, van Broekhoven and Wilts reported on the measurement of BHR using the tcPO 2 method; they described its convenience and safety in young children. 12,25 During acute attacks of asthma, it is known that changes in tcPO 2 are linearly related to the severity of the asthma attacks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11,15 Recently, van Broekhoven and Wilts reported on the measurement of BHR using the tcPO 2 method; they described its convenience and safety in young children. 12,25 During acute attacks of asthma, it is known that changes in tcPO 2 are linearly related to the severity of the asthma attacks.…”
Section: Discussionmentioning
confidence: 99%
“…Using a tcPO 2 -monitoring method described elsewhere, 11,14 we performed methacholine inhalation challenge on all of the subjects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a decrease in Dmin or in PD 35 -Grs indicates an increase in airway hyperresponsiveness, and an increase in Dmin or in PD 35 -Grs indicates a decrease in airway hyperresponsiveness. Previous studies have reported a significant correlation between the bronchial hyperresponsiveness measured by an astograph and those measured by conventional methods, and showed the clinical usefulness of the astograph [14,15,16,17]. …”
Section: Methodsmentioning
confidence: 99%